Vinculum of sustainable development goal practices and firms' financial performance: A moderation role of green innovation - Parvez Alam Khan; Satirenjit Kaur Johl; Shakeb Akhtar (Journal of Risk and Financial Management, 2022)
The 2030 Agenda for Sustainable Development (SDGs) has been established to alter our world by addressing the challenges faced by humanity in order to promote wellbeing, economic prosperity, and the protection of the environment. The SDGs provide a holistic and multi-dimensional approach to development compared to conventional development plans that focus on a limited range of dimensions. As a result, linkages between the SDGs may result in differing outcomes. This research is the first to investigate the direct relationship of environmental and social SDGs with firms' financial performance and the moderating role of green innovation. Data from 67 companies from five continents (Europe, Australia and New Zealand, Asia, North America, and Africa) and their top five blue-chip firms were collected through content analysis. Generalized least squares (GLS) were used to test for direct relationships. The results showed a positive correlation between environmental SDGs and the negative significance of social SDGs on firms' financial performance. However, mixed findings regarding the moderation variable green innovation over SDGs and firms' financial performance were found. The new findings extend the SDG literature and provide empirical evidence to practitioners and policymakers.
Keywords: 330; green innovation; sustainable development goal; environmental policy; financial performance; environment and social